Dental caries and its association with the oral microbiomes and HIV in young children-Nigeria (DOMHaIN): a cohort study - Modupe O. Coker; Paul Akhigbe; Esosa Osagie; Nosakhare L. Idemudia; Oghenero Igedegbe; Nneka Chukwumah; Ruxton Adebiyi; Allison E. Mann; Lauren M. O'Connell; Ozo Obuekwe; Augustine Omoigberale; Manhattan E. Charurat; et al. (BMC, 2021)
Abstract Background This study seeks to understand better the mechanisms underlying the increased risk of caries in HIV-infected school-aged Nigerian children by examining the relationship between the plaque microbiome and perinatal HIV infection and exposure. We also seek to investigate how perinatal HIV infection and exposure impact tooth-specific microbiomes' role on caries disease progression. Methods The participants in this study were children aged 4 to 11 years recruited from the University of Benin Teaching Hospital (UBTH), Nigeria, between May to November 2019. Overall, 568 children were enrolled in three groups: 189 HIV-infected (HI), 189 HIV-exposed but uninfected (HEU) and 190 HIV-unexposed and uninfected (HUU) as controls at visit 1 with a 2.99% and 4.9﻿0% attrition rate at visit 2 and visit 3 respectively. Data were obtained with standardized questionnaires. Blood samples were collected for HIV, HBV and HCV screening; CD4, CD8 and full blood count analysis; and plasma samples stored for future investigations; oral samples including saliva, buccal swabs, oropharyngeal swab, tongue swab, dental plaque were collected aseptically from participants at different study visits. Conclusions Results from the study will provide critical information on how HIV exposure, infection, and treatment, influence the oral microbiome and caries susceptibility in children. By determining the effect on community taxonomic structure and gene expression of dental microbiomes, we will elucidate mechanisms that potentially create a predisposition for developing dental caries. As future plans, the relationship between respiratory tract infections, immune and inflammatory markers with dental caries in perinatal HIV infection and exposure will be investigated.